The article concerns the role of technologies assisting the work of people with disability, especially in telework - Grzegorzewska, Maria Katarzyna; Karocki, Piotr (Niepełnosprawność i praca: Wymiary, konteksty, perspektywy, 2024)
The aim is to: raise awareness of these technologies and their potential to increase employment opportunities and independence for people with various types of disabilities. The problem is the lack of availability of the discussed technologies and knowledge about them.Method: literature review and analysis of various assistive technologies available on the market. The results show that many assistive technologies, such as communication tools, information accessibility technologies, and mobility and computer access technologies, can help people with disabilities perform professional tasks while teleworking.In summary, assistive technologies can significantly improve employment opportunities and independence for people with disabilities. However, their effective implementation requires taking into account the individual needs and preferences of users and providing appropriate training and support.